Palygorskite-supported sulﬁde-modiﬁed nanoscale zero-valent iron for Congo red removal. Issue 1 (1st January 2019) - Quan, Guixiang; Yang, Ming; Fan, Qinya; Wang, Hui; Yan, Jinlong
ABSTRACT: In this work, the optimum conditions for the synthesis of nano zero valent iron sulfide were studied in detail using orthogonal experiment. The palygorskite-supported sulﬁde-modiﬁed nanoscale zero-valent iron (S-nZVI/P) was prepared, characterized, and further applied to remove Congo red (CR) in aqueous solutions. The results of structural characterization showed that the Fe 0 was coated with FeS layers. The influence of sulfidation conditions on the removal rat e of CR was investigated in detail, and the results revealed that S-nZVI/P prepared at 30°C with a Fe/S ratio of 1 was found to effectively remove CR. Moreover, S-nZVI/P showed a significantly enhanced removal rate towards CR as compared with nZVI/P and nZVI, suggesting that sulfidation treatment is a promising method to improve the reactivity of nZVI.